The Boundary Conditions of Export Relational Governance: A "Strategy Tripod" Perspective. Issue 2 (June 2014) - Ju, Min; Zhao, Hongxin; Wang, Tiedong
Manufacturers often use relational governance to manage interfirm relationships with their distributors. Yet recent literature has cautioned that relational governance may only offer conditional benefits. In this study, the authors integrate the resource-, industry-, and institution-based views to examine whether there is a limit to the positive effect of relational governance on export performance. Furthermore, the authors investigate two conditioning factors: industry uncertainty and cross-national institutional distance. Using a survey of 184 export ventures from China, the authors find that relational governance has an inverted U-shaped relationship with performance. In addition, the findings show that the export performance effect of relational governance becomes less effective in uncertain industry environments, but cross-country institutional distance enhances the value of relational governance.